2020
DOI: 10.3389/fonc.2020.00261
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Ratio of Immune-Related Colitis, Hepatitis, and Pancreatitis in Patients With Solid Tumors Caused by PD-1/PD-L1 Inhibitors: A Systematic Review and Meta-Analysis

Abstract: Purpose: The meta-analysis was put into practice in evaluating the risk ratio of immune-related digestive system inflammation in patients with solid tumors caused by PD-1/PD-L1 inhibitors.Method: The process of the meta-analysis was performed by us according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines.Results: After screening and eligibility assessment, a total of 26 clinical trials involving 16,409 patients were selected for the final quantitative synthesis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The PRISMA flow diagram was shown in (Figure 1), while the bias assessment summary of all enrolled clinical trials were provided in (Supplementary Figure 1). A total of 589 published studies was found by PubMed search, while 37 studies were gotten from the former published meta-analysis (61)(62)(63). After eligibility assessment, 5 articles were only used for the systematic review (13,(20)(21)(22)(23), while 42 articles were used for the final comprehensive analysis (4-12, 14-19, 24-50).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The PRISMA flow diagram was shown in (Figure 1), while the bias assessment summary of all enrolled clinical trials were provided in (Supplementary Figure 1). A total of 589 published studies was found by PubMed search, while 37 studies were gotten from the former published meta-analysis (61)(62)(63). After eligibility assessment, 5 articles were only used for the systematic review (13,(20)(21)(22)(23), while 42 articles were used for the final comprehensive analysis (4-12, 14-19, 24-50).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Dual checkpoint inhibition induced by combination therapy with nivolumab and ipilimumab improves response rates in patients with metastatic melanoma compared to monotherapy. However, a higher rate of toxicity, including immune-related colitis, seems to be present under this regimen showing itself as ICI-induced diarrhea [5, 10]. Diagnostic colonoscopy and multiple colonic biopsies are necessary for the diagnosis of ICI-induced colitis, as a diversity of clinical, endoscopic and histological manifestations have been observed in patients with ICI-induced diarrhea [10].…”
Section: Discussionmentioning
confidence: 99%
“…A T cell-mediated immune response is probably involved in the ICI-induced colitis, as infiltration with CD8 + cells and T-bet expressing CD4 + cells has been observed in the colon biopsies of patients receiving nivolumab [4]. A meta-analysis by Tian et al [5] reported an increased incidence risk of all grade colitis in patients with solid tumors receiving ICIs, compared to those undergoing chemotherapy or chemotherapy and ICIs. The lower incidence risk was observed under monotherapy with nivolumab [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the improved safety profile, greater attention should be given to the special irAEs of anti‐PD therapy, which can be fatal. IrAEs most commonly affect the gastrointestinal tract, endocrine glands, skin, and liver [ 302 ], but severe pneumonitis, myocarditis, colitis, hepatitis and neurological toxicities can also occur and lead to a dismal prognosis [ 303 , 304 , 305 , 306 , 307 ]. For instance, fulminant ICI‐related myocarditis has been reported to increase in occurrence with the increased use of ICIs [ 304 ].…”
Section: Controversies and Limitations Of Cancer Immunotherapymentioning
confidence: 99%